2011
DOI: 10.1258/msl.2011.011021
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of dental age and its comparison with chronological age: accuracy of two radiographic methods

Abstract: Despite the favourable result of Willems' method in comparison with Demirjian's method, this study demonstrated a high correlation coefficient between both chronological and obtained dental age, thus confirming their potential applicability in clinical practice and forensic dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 15 publications
3
44
0
Order By: Relevance
“…The overestimation of dental age varied between 0.78 to 1.97 years for boys (mean 0.35 years), and 0.86 to 1.31 years for girls (mean 0.39 years), indicating that the females may show earlier maturation in dental development than the males. Considering mean differences between estimated dental ages and chronological ages, most authors have also found statistically significant differences of 0.681 years and 0.616 years [26], 0.4 years and 0.6 years [7], 0.3 years and 0.4 years [35], 0.75 years and 0.61 years [4], 0.34 years and 0.25 years [36], 0.66 years and 0.56 years [23] in boys and girls, respectively. Moreover, when a stratified analysis based on ethnicity was conducted, an average overestimation of 0.28 years and 0.38 years were found in Asian and Caucasian boys, and 0.24 years and 0.52 years were found in Asian and Caucasian girls, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The overestimation of dental age varied between 0.78 to 1.97 years for boys (mean 0.35 years), and 0.86 to 1.31 years for girls (mean 0.39 years), indicating that the females may show earlier maturation in dental development than the males. Considering mean differences between estimated dental ages and chronological ages, most authors have also found statistically significant differences of 0.681 years and 0.616 years [26], 0.4 years and 0.6 years [7], 0.3 years and 0.4 years [35], 0.75 years and 0.61 years [4], 0.34 years and 0.25 years [36], 0.66 years and 0.56 years [23] in boys and girls, respectively. Moreover, when a stratified analysis based on ethnicity was conducted, an average overestimation of 0.28 years and 0.38 years were found in Asian and Caucasian boys, and 0.24 years and 0.52 years were found in Asian and Caucasian girls, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…30 Dental development is assessed through development and eruption of all teeth. 31 and the third molar is the only parameter of tooth maturation until a later age. 32 Some studies claim that dental development shows less variability than other developmental features 5,31 and proved to have a substantial biological stability from extreme nutritional conditions.…”
Section: Biological Methods In Use For Evidence Of Age Of Majoritymentioning
confidence: 99%
“…A recent study by RB Mohammed et al, conducted among South Indian children who concluded that mean dental age showed significant underestimation of 0.7 ± 1.69 years and 0.11 ± 1.3 years in boys and girls respectively [26]. However a study conducted among North Indian population by Grover et al reported that the method overestimated age of girls and boys by 0.24 and 0.36 years respectively [20].…”
Section: Year Of Birthmentioning
confidence: 98%
“…Therefore, Ozle et al regarded Demirjian's system to be the best for dental age estimation [23]. However, modified Demirjian's method proposed by Willem's has been tested in various geographic population groups and has shown higher accuracy than Demirjian's method dental age estimation [20,24]. The accuracy of Willem's method can be contributed to its single step calculation from the gender specific chart.…”
Section: Year Of Birthmentioning
confidence: 99%
See 1 more Smart Citation